ANALYSIS OF THE EFFECTS OF ORGANIZATIONAL COMMITMENT MEDIATION ON THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF PT SARANA LINTAS CARAKA - Netty Laura Simbolon; Budi Satriyo Priyonggo (STKIP Singkawang, 2022)
A company cannot develop optimally if it is not fully supported by qualified and advanced human resources within the company, including by PT Sarana Lintas Caraka. The purpose of this study was to examine the mediating effect of organizational commitment on the effect of transformational leadership style and organizational culture on the performance of employees of PT Sarana Lintas Caraka. The research method used in this research is quantitative with Partial Least Square (PLS-SEM) technique and assisted by SmartPLS 3.0 software. The researcher chose the census technique in the sampling technique, namely all members of the population (all PT Sarana Lintas Caraka) were used as samples in this study to examine the mediating effect and the direct influence of the related variables. The results of this study indicate that Transformational leadership style does not affect employee performance, the influence of organizational culture on employee performance, the influence of organizational commitment on employee performance, the influence of transformational leadership style on organizational commitment, the influence organizational culture on organizational commitment, organizational commitment can mediate organizational culture on employee performance. Organizational commitment can mediate transformational leadership style on employee performance. The method of determining the number of respondents' eligibility is using the Hair Method which states that the respondent may be 5 to 10 times the number of research variable indicators.